Outcomes, Prognostic Factors and Salvage Treatment for Recurrent Chordoma After Pencil Beam Scanning Proton Therapy at the Paul Scherrer Institute. Issue 8 (August 2020) - Beer, J.; Kountouri, M.; Kole, A.J.; Murray, F.R.; Leiser, D.; Kliebsch, U.; Combescure, C.; Pica, A.; Bachtiary, B.; Bolsi, A.; Lomax, A.J.; Walser, M.; et al.
Abstract: Aims: The outcome of chordoma patients with local or distant failure after proton therapy is not well established. We assessed the disease-specific (DSS) and overall survival of patients recurring after proton therapy and evaluated the prognostic factors affecting DSS. Materials and methods: A retrospective analysis was carried out of 71 recurring skull base ( n = 36) and extracranial ( n = 35) chordoma patients who received adjuvant proton therapy at initial presentation ( n = 42; 59%) or after post-surgical recurrence ( n = 29; 41%). The median proton therapy dose delivered was 74 GyRBE (range 62–76). The mean age was 55 ± 14.2 years and the male/female ratio was about one. Results: The median time to first failure after proton therapy was 30.8 months (range 3–152). Most patients ( n = 59; 83%) presented with locoregional failure only. There were only 12 (17%) distant failures, either with ( n = 5) or without ( n = 7) synchronous local failure. Eight patients (11%) received no salvage therapy for their treatment failure after proton therapy. Salvage treatments after proton therapy failure included surgery, systemic therapy and additional radiotherapy in 45 (63%), 20 (28%) and eight (11%) patients, respectively. Fifty-three patients (75%) died, most often from disease progression (47 of 53 patients; 89%). The median DSS and overall survival after failure was 3.9 (95% confidence interval 3.1–5.1) and 3.4 (95% confidence interval 2.5–4.4) years, respectively. On multivariate analysis, extracranial location and late failure (≥31 months after proton therapy) were independent favourable prognostic factors for DSS. Conclusion: The survival of chordoma patients after a treatment failure following proton therapy is poor, particularly for patients who relapse early or recur in the skull base. Although salvage treatment is administered to most patients with uncontrolled disease, they will ultimately die as a result of disease progression in most cases. Highlights: The survival of chordoma patients who recur after proton therapy is poor. Local relapse is the predominant site of recurrence. Most patients receive salvage therapy, but only a minority can be cured. Skull base tumours and early relapse after proton therapy predict poor prognosis.